Repeat corneal graft failure due to graft-to-host herpetic infection - Gatzioufas, Zisis (Springer, 2013)
BACKGROUND: Herein, we present the case of a young female patient with keratoconus, who was subjected twice to repeat keratoplasty, and each time, she experienced a corneal graft failure. FINDINGS: Under the suspicion of herpetic eye disease, we administered topical and systemic anti-herpetic treatment after the second repeat keratoplasty. The postoperative course was uneventful, and the corneal graft is clear, until recently. Immunohistochemistry and DNA-polymerase chain reaction were negative for herpes simplex virus-1 (HSV-1) in the host cornea, but they detected HSV-1 in both transplanted corneal grafts, thereby supporting our clinical hypothesis that graft-to-host HSV-1 infection elicited this chain reaction of complications in our patient. CONCLUSION: This clinical report illustrates in a unique way the dramatic impact an unsuspected herpetic infection in the corneal graft in cases of keratoplasty may have and underscores the necessity of suspecting and adequately treating these distinct cases.